2022
DOI: 10.3389/fpubh.2022.906788
|View full text |Cite
|
Sign up to set email alerts
|

First-Year College Students' Mental Health in the Post-COVID-19 Era in Guangxi, China: A Study Demands-Resources Model Perspective

Abstract: The post-COVID-19 era means that the COVID-19 is basically under control; however, the risk of the pandemic still affects people's work, study, and life, physically and psychologically. In this era, due to the more challenges first-year college students face, more attention should be paid to their mental health. An emerging study demands-resources (SD-R) model can explain the influencing mechanism of college students' mental health. This model suggests that study demands increase the risk of student burnout, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 88 publications
2
14
0
2
Order By: Relevance
“…Not only because it is more effective for the learning process, but also because a network of relationships can be generated that facilitates integration and confidence in oneself and colleagues [ 39 , 40 ]. Studies in this line of work showed that there is a significant decrease in the quality of emotional and affective implications, due to the lack of face-to-face communication between students and, therefore, the loss of quality of relationships between people (student–student or student–instructor) in a more solitary online environment that requires a higher level of development [ 41 ]. The challenges students faced during this period, such as study demands, time pressure, emotional exhaustion, perceived social support, or student engagement, may explain the influencing mechanism of students’ mental health and this impact on the perceived difficulty to learn during the face-to-face classes.…”
Section: Discussionmentioning
confidence: 99%
“…Not only because it is more effective for the learning process, but also because a network of relationships can be generated that facilitates integration and confidence in oneself and colleagues [ 39 , 40 ]. Studies in this line of work showed that there is a significant decrease in the quality of emotional and affective implications, due to the lack of face-to-face communication between students and, therefore, the loss of quality of relationships between people (student–student or student–instructor) in a more solitary online environment that requires a higher level of development [ 41 ]. The challenges students faced during this period, such as study demands, time pressure, emotional exhaustion, perceived social support, or student engagement, may explain the influencing mechanism of students’ mental health and this impact on the perceived difficulty to learn during the face-to-face classes.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement in learning is widely defined as the level of energy, focus, and dedication an individual exhibits when engaged in learning activities ( Wei et al, 2022 ). Based on these definitions, this study adapted Schaufeli et al’s (2002) Work Engagement Questionnaire (WE), with nine questions, to assess the engagement of university students in online sustainable learning during the post-epidemic period.…”
Section: Methodsmentioning
confidence: 99%
“…Study resources include environmental resources (e.g., perceived teacher support, classroom climate, etc. ), personal resources (e.g., academic self-efficacy and psychological resilience), and learning behaviors including learning engagement ( Wei et al, 2022 ). Thus, PTS can be considered as an environmental resource, OAS-E and academic emotions can be considered as personal resources, and SOLE and OAP can be considered as learning outcomes and behaviors.…”
Section: Research Model and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations